Oral Literature and Globalization: The Case of Mbum Land - Doreen Mekunda; Mereal Njamnsi Nkfunji (European Scientific Journal, ESJ, 2025)
In Cameroonian societies like elsewhere in Africa, people narrate their history of origin linked to myths and legends. Mbum history of ancestry have been written using oral tradition as the memories of the past are embedded in the songs, folktales and proverbs of the people.  The work explores the multi-faceted relationship between oral literature and globalization, examining how globalization impacts the preservation, adaptation and cross-cultural exchange of the Mbum oral tradition. While Globalization poses challenges to the authenticity and continuity of the Wimbum oral literature, it also presents opportunities for revitalization and wider dissemination, and it is built around the contention that, while oral literature is rooted in the people’s cultural practices, its only medium of transmission is by word of mouth. Ethno-criticism and cultural materialism have been used in understanding and navigating the complex dynamics between oral literature and globalization. The intersection of oral literature and globalization in Wimbum land presents both challenges and opportunities for the preservation and promotion of Wimbum cultural heritage, thus the questions:  What challenges does oral literature face in the era of globalization? How can oral literature be preserved so as to continue to serve in the globalized era? How effective are folklore in the face of these global threats? What strategies can be put in place for survival of Mbum Oral tradition? These researchers went to the field, collected and analyzed the effectiveness of some folklore elements (folktales, proverbs, and folksongs) as communicative tools. The findings revealed that, the continuity of the performance of Mbum oral literature has changed and its aesthetic qualities have been innovated due to the effects of globalization.